An adoption of improved varieties of kachri (Cucumis melo var. callosus) in hot arid region of Rajasthan: An impact assessment (Indian Journal of Arid Horticulture, 2018)
The present study was conducted in all 12 districts of hot arid region of Rajasthan during last 10 years (2007 -2017). These  districts were purposively selected for the study as the farmers of these district have adopted the improved variety (AHK-119) of  kachri and was grown extensively during kahrif/summer season of the year. An extensive study was conducted to assess the  impact of adoption of this improved variety and it was found that the average production of the improved variety was 89 q/ha  while that of local variety (local check) was 64.0 q/ha. This illustrate that average production of improved variety of kachri  (AHK-119) was 39.06 % higher than the production of local one. Per hectare net return from the improved variety of kachri  (AHK-119) was 107.35 % higher than the net return achieved from the local variety of kachri. The total area under cultivation of  improved variety AHK-119 of kachri in entire hot arid region of Rajasthan was 1277 ha in 2007 which increased to 3865 ha in the  year 2017. The gross return from the improved variety of kachri (AHK-119) in entire hot arid region of the Rajasthan was 17.50  corers in 2007 which increased to 52.97 crores in 2017. Likewise the net return from the improved variety of kachri (AHK-119) in  entire hot arid region of Rajasthan was 12.88 crores in 2007 which increased to 38.98 corers in 2017 i.e. increased three times in  2017 in comparison to the year 2007. There were observed several progressive farmers who multiplied/produced the seed of  improved variety of kachri (AHK-119) under the scientific guidance of the scientist of the Institute (ICAR-CIAH, Bikaner) and  sold it @ Rs. 2000 3000 or more per kg to other needy farmers/clients to earn money.
Keywords: Adoption; production; improved variety; kachri; impact assessment; hot arid region